ANALYSIS ECONOMIC IMPACT OF PAYA BAKUNG BRIDGE CONSTRUCTION ON ACCESSIBILITY PATTERNS AND FARMERS' WELFARE - Ulina, Reh; Putra, Ilham Mirzaya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Rural infrastructure development plays a crucial role in improving community welfare, particularly for farmers who rely heavily on transportation access to distribute their agricultural products. This study aims to analyze the impact of bridge construction on changes in accessibility and farmer welfare in Paya Bakung Village, Hamparan Perak District. This study employed a qualitative approach using descriptive analysis methods. Five informants, including landowners and farm laborers, were selected through purposive sampling. Data were collected through in-depth interviews, field observations, and documentation. Data analysis employed the Miles and Huberman interactive model, which encompasses data reduction, data display, and conclusion drawing. Validity was ensured through source triangulation. The results indicate that bridge construction significantly improved community accessibility. Travel time to market was shortened, transportation costs decreased, and crop quality was maintained, resulting in more stable selling prices. These changes contributed to increased household incomes for farmers, reduced workloads for farm laborers, and strengthened social relations within the village community. From an Islamic societal development perspective, these improvements reflect the achievement of the concept of Falah, which refers to material and spiritual well-being characterized by increased security, solidarity, and social cohesion. Therefore, bridge construction not only functions as physical infrastructure but also as an instrument of community empowerment that contributes to improving the economic and social welfare of rural communities.